Effects of Dysmenorrhea on Academic Activities among Higher Secondary Students of selected College in Kathmandu - Paudel, Radha; Shrestha, Sarita (Journal of Karnali Academy of Health Sciences, 2020)
Background: Dysmenorrhea is the most common complaint and a leading cause of absenteeism in adolescence among university female students. It affects social, academic, and sports activities. Therefore, the objective of the study was to find out the effects of dysmenorrhea on academic activities among higher secondary students.Methods: A descriptive cross-sectional study was conducted among higher secondary female students. A purposive sampling technique was used and the sample size was 206. Data collection was done from January 15, 2020, to February 12, 2020. Data were collected from the semi-structured questionnaire through a selfadministered technique. The frequencies, percentage, mean, standard deviation, and range were used as a part of descriptive statistics. The Chi-square test and Fischer’s exact test was used to establish the association between categorical variables. P value less than 0.05 was used for statistical significance.Result: The findings showed that the dysmenorrhea was 92.2% whereas, 45.3%, 23.7%, and 31%, of students had severe, moderate, and mild pain respectively. Likes as 74.2% had an average academic activity. There was a statistical association of pain with college absenteeism, class absenteeism, unable to study in the exam, and lack of interest in sports (P